Altered expression of IRS2 and GRB2 in demyelination of peripheral neurons: Implications in diabetic neuropathy. (April 2017) - Manu, Mallahalli S.; Rachana, Kuruvanthe S.; Advirao, Gopal M.
Abstract: Demyelination of the peripheral nerves and dysfunction of Schwann cells (SCs) are the chronic complications involved in the development of peripheral neuropathy among diabetic patients. Insulin signaling plays an important role in restoring the myelin proteins in diabetic peripheral neuropathy (DPN). Since insulin levels are altered in diabetes, it becomes of great interest to appreciate the role and regulation of docking and adaptor protein, how these proteins respond to variations in the levels of insulin as experienced in juvenile diabetes. Tyrosine phosphorylation of receptor protein kinases provides a docking site for the activation of adaptor proteins which are the key regulators of insulin signaling pathway. In this report, we studied the long term effect of insulin as a neurotrophic factor and identified the isoform of receptor substrate involved in the propagation of insulin signal in SCs. We also studied the ability of insulin to regulate the expression of different receptor substrates like insulin receptor substrate-1 (IRS1), insulin receptor substrate-2 (IRS2) and growth factor receptor-bound protein-2 (GRB2) that propagate the insulin signaling and also their variation in hyperglycemic SCs and sciatic nerve of the diabetic rats. Results confirmed that IRS2 is the key receptor substrate involved in insulin signal transduction. But, a radical increase in the phosphorylation of IRS2 at serine 731 prevents the recruitment of GRB2 adaptor protein which may fail further to connect the Ras and other pathways required to the cell for its survival and to maintain integrity. These findings prove that SCs and sciatic nerve express IRS proteins that are altered by diabetes and thereby insulin signaling downstream is impaired and that contribute to the pathogenesis of DPN. Graphical abstract: Highlights: Insulin signal is required to maintain myelin sheath in DPN. Altered expression of receptor substrates with significant elevated phosporylation of IRS2 at serine 731 in DPN. Decreased GRB2 activation in response to insulin in DPN